L-Plastin Expression in HCT 116 Colorectal Cells increases migration and ROS in an NADPH Oxidase-dependent manner - Long, Aideen (My University, 2022)
Objective: L-plastin is an action-bundling protein normally expressed in cells of haemopoietic origin but is also associated with malignant transformation. Aberrant expression of L-plastin expression correlates with tumour stage in colorectal cancers, and ectopic expression of L-plastin in colon cancer cell lines increases proliferation and migration. L-plastin is inducibly phosphorylated on Ser5 in response to a range of stimuli but the role of phosphorylated L-plastin in colon cancer cells has not been characterised. The aim of this study was to analyse the effect of L-plastin Ser5 phosphorylation on HCT 116 colon cancer cell proliferation and migration. Methods: Wild-type L-plastin or a Ser5 L-plastin mutant where serine was exchanged to a non-phosphorylatable alanine was expressed in HCT 116 cells. Cell proliferation was assessed through cell counting and cyclin D activation. Cell migration were assessed using transwell migration assays. Results: We found that wild-type L-plastin was constitutively phosphorylated on Ser5 when expressed in HCT 116 cells and promoted an increased proliferation rate of these cells. HCT 116 cells stably expressing wild-type L-plastin also increased the migratory capacity of these cells together with increased levels of reactive oxygen species. NADPH oxidases are the main intracellular sources of reactive oxygen species and inhibition of NADPH oxidase activity with the pharmacological inhibitor DPI decreased the migration of these cells. Interestingly, expression of an L-plastin mutant with a non-phosphorylatable alanine in place of Ser5 did not promote increased cellular proliferation, indicating that phosphorylation is required for this process. In contrast, cellular migration and ROS production were independent of the phosphorylation status of Ser5. Conclusion: These data demonstrate that expression of L-plastin in HCT 116 colon cancer cells increases migration in a manner that is dependent on NADPH oxidase but independent of the Ser5 phosphorylation status.
PUBLISHED
Keywords: Colon cancer; L-plastin; Phosphorylation; Reactive oxygen species; Migration; Cancer; Immunology, Inflammation & Infection; Other; Health